Natural Resources With Comic-Based Learning Media - Liniasari, Anak Agung Ayu Made; Yudiana, Kadek; Dibia, I Ketut (International Journal of Elementary Education, 2021)
The limitations of learning media in the learning process are mainly in the content of social science with the topic of natural resources in grade IV. This study aims to develop valid comic-based learning media. The development model used is the ADDIE model which has five stages, namely: analysis, planning, development, implementation, and evaluation. Comic-based learning media products were the subject of this study, then the validity of comic-based learning media was the object of research. The data collection method was conducted using a questionnaire method. In measuring the validity of comic-based learning media, a rating scale instrument is used in the form of a media validity assessment sheet filled in by 1 lecturer as a material expert and 1 lecturer as a media expert and 2 teachers as a practitioner expert. The media validity data obtained were then analyzed using the mean formula to determine the average score of the validity of comic-based learning media. The average score obtained by each expert on the material expert is 4.80, the media expert is 4.79, and the practitioner expert is 4.88, the three average scores obtained belong to the "very good" category. Based on this, the comic-based learning media developed on the topic of natural resources is declared valid and can be used in learning in grade IV elementary schools.